1963
DOI: 10.1172/jci104794
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Changes in the Pulmonary Vascular Bed Produced by Atropine, Pulmonary Engorgement, and Positive-Pressure Breathing on Diffusing and Mechanical Properties of the Lung*

Abstract: Several factors probably have some role in determining the volume of the effectively ventilated pulmonary capillary bed, including pulmonary blood flow, pulmonary vascular pressures, pulmonary blood volume, alveolar and blood gas tensions, and mechanical effects of ventilation.Others have found that atropine sulfate, 2.0 mg iv, increases cardiac output (1, 2), decreases central venous pressure (1, 2), and affects the distribution of the blood volume as shown by plethysmographic study of extremity venous volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0

Year Published

1965
1965
1992
1992

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…Acute pulmonary vascular engorgement increases the volume of the pulmonary capillary bed either by recruiting such previously inactive capillaries or by dilating ones already in use (3,4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Acute pulmonary vascular engorgement increases the volume of the pulmonary capillary bed either by recruiting such previously inactive capillaries or by dilating ones already in use (3,4).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in right atrial pressure were used as an index of changes in transmural pulmonary capillary pressure. Evidence available from studies in normal men suggests that acutely induced increases in right atrial, pulmonary arterial, and pulmonary "wedge" pressures are equivalent (4,21). Similar results have been produced during acute changes in central vascular pressures in dogs (22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that increases in pulmonary blood flow alone do not increase DLco (1,5,6). Theoretic considerations predict that Dr0o should be relatively independent of pulmonary capillary blood flow but quite sensitive to the instantaneous volume of blood exposed to the alveolar gas (7).…”
mentioning
confidence: 99%